Development of pre- and post-match morning recovery-stress states during in-season weeks in elite youth football - Pelka, M.; Schneider, P.; Kellmann, M. (Science and Medicine in Football, 2018)
Objectives: The aim of this study was to examine how matches affect self-report measures of physical, mental, and emotional states in order to set a base for developing specific recovery approaches. Methods: A total of 25 players (Mage = 17.5, SD = .5 yrs.) of an U19-Junioren-Bundesliga team participated over the entire 6-month assessment period. The players completed the Short Recovery and Stress Scale twice a week on Monday and Friday mornings between 7 and 9am. During the assessment period the players participated in 12 match days. Results: Wilcoxon signed-rank tests revealed significant main effects for changes from Friday to Monday ratings in players who played more than 60 min (regular players) and less than 60 min (substitutes). The regular players were more physically and mentally stressed after matches whereas the substitutes experienced higher emotional stress when comparing Mondays` and Fridays` stress ratings. Conclusions: Therefore, matches affect those who played more than 60 min differently compared to those who played less than 60 min. This was the case not only for physical recovery-stress ratings but also for mental, emotional and overall self-reports. Consequently, coaches should take the self-ratings of their players into account to create efficient training regimens to prevent negative consequences such as underrecovery or overtraining.